The Impact of Trust and Quality of Electronic Services on Digital Bank Customer Satisfaction with the Bank Image as a Mediator - Andyan Pradipta Utama; Nana Trisnawati (Jurnal Syntax Transformation, 2024)
The COVID-19 pandemic and the development of information technology use in recent years have caused changes in people's behavior patterns and preferences in using digital services. This indirectly encourages the emergence of an accelerating trend of digital transformation in the bank sector in 2022, where banks massively optimize the use of digital technology in both customer products and services. This research is motivated by the development of digital banks which have become a phenomenon in the financial industry in recent years, with the needs of customers who want the speed and flexibility of bank services that are available anywhere and anytime. Customer satisfaction not only supports the survival of the bank, but also the development of the bank. Customer satisfaction in the bank is influenced by many factors such as trust because the bank operates based on the principle of customer trust, the quality of service that must be provided continuously and without interruption, and the image or image of the bank itself. Based on the above phenomenon, this study aims to analyze the role of the bank's image as a mediator of the impact of trust and quality of electronic services on digital bank customer satisfaction. The population of this study is digital bank customers located in DKI Jakarta, with a sample of 190 people. The data analysis method using the Structural Equation Model (SEM) is processed with SmartPLS version 3.29. In this study, it is known that trust does not affect customer satisfaction, the factors that make customers satisfied are the quality of service and the image of the bank.